Jan Jakub Rousseau w naturze/ogrodzie? Dyskursy natury we współczesnych odczytaniach feministycznych i posthumanistycznych - Lucyna Kopciewicz (Problemy Wczesnej Edukacji)
The 21st century is called ‘the biotech age’. We cannot deny the emergence of significant changes in the way we conceive nature and ourselves. The main influence comes from biotechnologies and information science which modify the definition of nature. This article focuses on Rousseau’s discourses of nature understood as moral and gendered bases of social order. Feminism and posthumanism significantly challenge these discourses and contribute to the development of postanthropocentric nature seen as a vital network of human and nonhuman agents.